The Implementation of Accrual Basis Accounting in Indonesian Local Government - Jonathan, Albertus Theo; Aswar, Khoirul; ., Ermawati (Journal of Economics and Behavioral Studies, 2020)
This study is based on the Government Regulation No 71 of 2010 concerning Government Accounting Standards which have been enacted since 2015. In the period of this regulation enactment, there are obstacles that occur and it causes culpabilities in accrual basis accounting reporting. The objective of this study is to discover the factors which affect the accrual basis accounting implementation. Utilizing institutional theory as the theoretical basis to establish the framework that correlate training, communication, educational background, organizational culture, and implementation of accrual basis accounting. This study was conducted using quantitative method in local government of Bekasi. Therefore, this study contributes to regional government in order to able to provide the input in implementing a policy, specifically the Government Accounting Standards; provide information in regard to the obstacles and solutions which affects the implementation accrual basis accounting in Regional Government; and be able to evolve and intensify the application of public sector governance, and also can be function as a suggestion for the public in creating policies and to ensure the fully-implementation in Regional Government